Smart LCD Proyektor Balancing Berbasis Android - Andi Pratama, Febrian; Ulum, Miftachul; Alfita, Riza (Jurnal FORTECH, 2020)
A The use of LCD projector as one of the supports media for teaching, and learning activity has been commonplace in the world of education today, for example at the University of Trunojoyo Madura. During this time, the LCD projector is very helpful in the learning process, especially for presentations and others. The LCD projector also very well utilized with the limitations of the remote, often the projector must be turned on manually, by hand or by using a long stick. For a long time, if this continues and is often done it can cause damage to the projector and can disrupt the teaching and learn process in the room. The solution in this case is to make a simulation tool and projector controller application that functions to turn on, turn off, kmow the slope and adjust the direction of movement on the projector. Furthermore, this application can be embedded on mobile devices, especially Android-based mobile phones. This tool uses the Bluetooth module, Arduino as a media connection between Android and Arduino. With the use of the application, it is expected to be implemented to avoid damage to the projector which is too often used manually and certainly will greatly assist the teaching and learn process, especially at the University of Trunojoyo, Madura.